CONTRASTING LIGAND PHOTOLABILISATIONS IN THE ACETYL COMPLEXES [(ETA(5)-C(5)R(5))FE(CO)(PPH(3))COME] (R=H, ME) - Davies, S; Watkins, W (1994)
While the primary photochemical process for [(η5-C 5H5)Fe(CO)(PPh3)COMe] is exclusive loss of carbon monoxide to generate [(η5-C5H 5)Fe(CO)(PPh3)Me], that for [(η5-C 5Me5)Fe(CO)(PPh3)COMe] is exclusive loss of triphenylphosphine to generate [(η5-C5Me 5)Fe(CO)2Me].